Cytotoxicity evaluation of sodium lauryl sulfate in a paper-based 3D cell culture system. Issue 18 (31st March 2022) - Lee, Young Ju; Ahn, Yong Jin; Lee, Gi-Ja
Abstract : The 3D cell culture paper provided an appropriate environment for the growth of L929 cells. Cytotoxicity of SLS to cells in the paper-based 3D culture system was similar to a commercial 3D cell culture kit, but more sensitive than 2D cell culture. Abstract : Because three-dimensional (3D) cell culture is more similar to in vivo cell microenvironments than two-dimensional (2D) cell culture, various 3D cell culture systems have been developed. Recently, paper has been used as a promising material for 3D cell culture and tissue models due to its flexibility, ease of manufacture, low cost, and widespread accessibility. In this study, we fabricated a paper-based 3D cell culture platform consisting of a hydrophilic region for cell attachment and a hydrophobic region printed with wax. Using this paper platform for 3D culture of L929 cells, we evaluated the cytotoxicity of a model substance, sodium lauryl sulfate (SLS), using water-soluble tetrazolium salt, Live/Dead, and luminescence assays. Then we compared those cytotoxicity results with results from a conventional 3D cell culture kit and 2D cell culture. We found that 3D cultured cells on paper responded more sensitively to SLS than 2D cultured cells, and the cytotoxicity of SLS to cells grown on the paper-based 3D cell culture platform was similar to that of cells grown using a commercially available 3D cell culture kit. Therefore, we expect that our paper-based 3D cell culture platform can be applied as a simple and facile tool for cell viability evaluation.